Balkan Colonists in the Azov Region: Diversity of Identities and Demise of the Ethnic Paradigm - Novik, Alexander A. (Vestnik Rossijskogo universiteta družby narodov. Seriâ Istoriâ Rossii (Print), 2024)
Through his work, the author analyzes the influence of state ideology and cultural codes on the ethnic and national self-identification of the migrants from Southeastern Europe to the Azov region of Russia. Through his research, he has revealed the degree of influence of various factors contributing to the sustainable preservation or loss of ethnic, regional, linguistic and religious identities within the framework of the development of a separate multi-ethnic territory. The source base for the study is the documents of the State Archive of the Rostov Region and the materials of complex expeditions, the Archive of the Museum of Anthropology and Ethnography of the Russian Academy of Sciences. The author comes to the conclusion, that at the present, most residents of the villages on the shores of the Taganrog Bay are well aware of the history of their settlements; many are ready to claim that they have Greek/ Arnaut roots, and therefore they resolutely declare their “autochthony.” However, there are no attempts to revitalize this traditional culture or it’s holidays - “like in Greece or Albania” (as it is happening in the Zaporozhye and Donetsk regions). In the region, belonging to one’s people, by those born and living there, is perceived as a more significant marker than ethnic origin, ethnic self-identification and declaration of ethnic preferences.